Level of knowledge of indigenous language, quechua, in the students at the Faculty of Medicine of the National University of San Marcos - Shimabuku Azato, Roberto (2018)
Mr. Editor, Quechua is the original language with the most users in Peru, with around 4 million speakers according to the 2007 census. It coexists with the Spanish language in many regions of the sierra, where it is the predominant language, and It is used daily by patients or users of health services. In the Faculty of Medicine of the National University of San Antonio Abad of Cusco, which began operating in 1980, Quechua is a compulsory course.87.1% of the graduates of the first eight promotions considered it important or very important to know that language1. Also, various publications in our environment, give an account of the importance of knowing native languages overcoming prejudices 2,3,4.